The Concept of Vitamin D Sufficiency and Insufficiency in Graves Disease (BIRDEM Medical Journal, 2017)
Graves disease (GD) is an autoimmune disorder of the thyroid gland resulting from dysregulation of the immune system against this important endocrine gland. The disease is characterized by hyperthyroidism and presence of circulation auto antibody which stimulates the Thyroid Hormone Receptor(TSHR). The auto antibody is also responsible for goiter and other extra-thyroidal manifestation like ophthalmic, dermatological and others. Vitamin D (Vit.-D) deficiency is reported to link with variety of autoimmune diseases. However the relation between thyroid autoimmunity of Graves disease and Vitamin D deficiency is still not very clear. But in some studies10-12, it was found that there is strong correlation between thyroid autoimmunity and vitamin D 1,25-(OH) deficiency in newly diagnosed GD. It was found < 15 pmol/L. In one study it was found